PERDAGANGAN SUATU BENTUK KEHIDUPAN EKONOMI KOTA - Perpustakaan UGM, i-lib ([Yogyakarta] : Program Studi Ilmu Keperawatan Fak. Kedokteran UGM, 2000)
ABSTRACT Connecting with colonial economical penetration in trade sector the company, which is market oriented, inclined concentrated in the city. Therefore Semarang as a city with very strategic location not only as a central government but also as an industrial development. It is no exaggeration if all of that is be one of the factors to appear migration and urbanization and is the main cause of urban affairs concentration and regional settlement.In the trade activity development, government gives a chance to various companies to establish their trade representative in Semarang. Many kinds of trade company that have a center at Semarang, having the system and trade net, which is organized professionally, majority owned and done by Europe Entrepreneurs. In Semarang the Europe Entrepreneurs are more active in the commercial agriculture enterprise authority, meanwhile Chinese Ethnic group extend the trade net further go to action of borrowing or lending money, wholesaler and staple supplies for export marketing.Semarang harbor market is an international market with hardly unlimited demands to many several of consumption good, either agriculture, manufacture industry or mine. Besides that market is one of community unit, having sense of involvement, propinquity and sense of possession, all of them are demonstrating the life of city. The market here is formed economical society activity in trade sector with the various good its mean trade or transaction.